Viability of folA-null derivatives of wild-type (thyA+) Escherichia coli K-12. - Krishnan, B R (1993)
Dihydrofolate reductase (the folA gene product) catalyzes the synthesis of tetrahydrofolate, a key methyl donor in many biosynthetic pathways. Loss of folA had been thought to be lethal to wild-type (thyA+) Escherichia coli. Viable folA-null derivatives of thyA+ E. coli were obtained, however, by recombining a folA deletion linked to a Kanr selectable marker into a lambda folA+ phage and using this phage to transduce cells to kanamycin resistance. folA-null strains were slow growing, formed small colonies, and were auxotrophic for thymidine, adenine, methionine, glycine, and pantothenate.